1994
DOI: 10.1007/bf00169827
|View full text |Cite
|
Sign up to set email alerts
|

Effects of imidazolines on noradrenaline release in rat isolated kidney

Abstract: The aim of the present study was to investigate whether or not activation of imidazoline receptors modulates noradrenaline release in the rat isolated kidney. Kidneys were pre-exposed to 3H-noradrenaline and the renal nerves were stimulated with 6 pulses at 100 Hz. The stimulation induced (S-I) outflow of radioactivity was taken as an index of endogenous noradrenaline release. The imidazoline derivatives clonidine (1-1000 nmol/l) and moxonidine (10-1000 nmol/l) inhibited S-I outflow of radioactivity with an EC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0
1

Year Published

1995
1995
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 21 publications
1
9
0
1
Order By: Relevance
“…25 Intrarenal infusion of moxonidine markedly increases urine flow rate, sodium excretion, and osmolar clearance 26 and modulates noradrenaline release in isolated rat kidneys. 27 The present study shows that in addition to the reported mechanisms by which moxonidine increases sodium and water excretion, moxonidine may also increase plasma ANP, which in turn would act on the kidney to cause diuresis and natriuresis through the release of cGMP. 28 Acute intravenous administration of moxonidine to normotensive rats dosedependently and significantly increased plasma ANP and enhanced diuresis, natriuresis, and kaliuresis as well as UcGMP, the index of ANP activity, thus implicating ANP in the renal actions of moxonidine.…”
Section: Discussionsupporting
confidence: 51%
“…25 Intrarenal infusion of moxonidine markedly increases urine flow rate, sodium excretion, and osmolar clearance 26 and modulates noradrenaline release in isolated rat kidneys. 27 The present study shows that in addition to the reported mechanisms by which moxonidine increases sodium and water excretion, moxonidine may also increase plasma ANP, which in turn would act on the kidney to cause diuresis and natriuresis through the release of cGMP. 28 Acute intravenous administration of moxonidine to normotensive rats dosedependently and significantly increased plasma ANP and enhanced diuresis, natriuresis, and kaliuresis as well as UcGMP, the index of ANP activity, thus implicating ANP in the renal actions of moxonidine.…”
Section: Discussionsupporting
confidence: 51%
“…Of note, the well-described renoprotective effects of ACE inhibitors are, at least in part, also mediated by a reduction in sympathetic activity. 9,67 Sympatholytic agents such as imidazoline receptor agonists, which act on I 1 -receptors in the brain stem and the kidney, 68,69 reduced glomerulosclerosis and albuminuria in a rat model of subtotal nephrectomy in the absence of any reduction in BP. 70 Studies of humans addressing this issue are scarce.…”
Section: Pharmacotherapymentioning
confidence: 99%
“…Presynaptic imidazoline receptors mediating an inhibition of noradrenaline release have been characterized in heart, aorta, pulmonary artery and kidney of different mammalian species Molderings et al 1991;Fuder and Schwarz 1993;Bohmann et al 1994). In most of these studies, the presence of imidazoline receptors could be detected only after blockade of presynaptic α 2 -adrenoceptors, suggesting the co-existence of both of these receptor sites on the same nerve terminals.…”
Section: Introductionmentioning
confidence: 99%